Izkopavanja srednjeveškega in zgodnjenovoveškega grobišča pri župni cerkvi v Kranju v letih 1964−1970 = Excavations of Medieval and Post-Medieval cemetery at the Župna cerkev in Kranj from 1964 to 1970 - Belak, Mateja; Pleterski, Andrej; Štular, Benjamin (Opera Instituti Archaeologici Sloveniae;Grobišče Župna cerkev v Kranju, 2016)
The archaeological excavations of the Župna cerkev cemetery in Kranj began in 1953 and were completed in 2013. The explored cemetery consists of 2,936 graves and the Museum of Gorenjska (Gorenjski muzej) in Kranj has inventoried 3,263 items from this cemetery.The purpose of the monograph is the publication of the graves excavated between 1964 and 1970 by Andrej Valič, curator at the Museum of Gorenjska. Data are drawn from all available sources (field documentation, artefacts, photographs, inventory books, analysis of skeletons, etc.).The plan of the graves, which took shape while studying the material, for the first time combines all the previously excavated graves of the Župna cerkev cemetery in Kranj. Because of the size of the cemetery and the high density of burials in some parts, the quadrants are shown by individual pages instead of the usual one-piece insert.The first part of the book is a study on the nature of the data presented, while the catalogue in addition to the usual data contains also comments on all potential oddities and inconsistencies.